The use of Arthrospira platensis in rearing Nile tilapia (Oreochromis niloticus) in salt water - Leite, Lorena; Quaresma, Fabrízia; Ribeiro, Pedro; Farias, Wladimir Ronald; Souza, Bartolomeu Warlene (Revista Ciência Agronômica, 2019)
Nile tilapia (Oreochromis niloticus) is a euryhaline species which, in marine systems, can provide animal protein where fresh water is scarce. As a result, adequate water management to maintain sustainability is essential, and the use of a salt water recirculating system would be an advantage at the present time. In addition, Arthrospira platensis is used in the diet of aquatic organisms, as it is rich in protein. The aim of this study, therefore, was to evaluate the use of A. platensis as a food supplement in the performance of Nile tilapia in a salt water recirculating system. The experimental model included two groups, with four replications. Each crop had a duration of 45 days (control and test), giving a total of 90 days, with the control being offered commercial feed, and the test crop commercial feed supplemented with 20% A. platensis meal. Water quality results showed that total ammonia (NH3) and phosphate (PO43-) levels remained high during cultivation. In zootechnical performance, specific growth rate and survival were higher in the control; on the other hand, for the percent composition of the filleted fish, the treatment supplemented with A. platensis had a higher level of protein. It is therefore possible to cultivate Nile tilapia in salt water at a salinity of 35 ppt.